PEDAGANG PASAR TRADISIONAL PINASUNGKULAN KAROMBASAN MANADO MENGHADAPI NEW NORMAL COVID 19 - Jobinus Kelabetme; Fonny Waani; Lisbeth Lesawengen (HOLISTIK, Journal of Social and Culture, 2021)
Corona virus disease 2019 (Covid-19) from Wuhan, Hubei Province of China (2020) spread over 190 countries. The spread of covid 19 shook Manado residents so that on April 28, 2020 Pinasungkulan Karombasan Manado market was designated as the new claster of Covid-19. There have been 10 patients confirmed positive for Covid-19 and two patients have died. At the beginning of the covid 19 outbreak, traditional market traders were upset about Pinasungkulan Karombasan Manado. Fear of exposure to coronavirus, merchandise is difficult to sell and must comply with health protocols facing the new normal.This study uses Qualitative Description approach with data collection techniques through observation, in-depth interviews and documentation. Materialist Theory Study William F. Ogburn that social change is based on technology.The results of this study found that the beginning of the covid 19 outbreak in general traders are confused to sell merchandise no consumers (buyers) and buyers are afraid of exposure to covid 19. Until the Task Force vigorously socializes following health protocols, namely washing hands, keeping distance and wearing masks. Traders began to sell and buyers began to return to shopping in the Pinasungkulan market. Now Pinasungkulan Manado traditional market traders are ready to face the new normal covid 19.Keywords: Traders, Traditional Markets, New normal covid 19